PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR IPS SISWA SEKOLAH DASAR - Isni Aise; Eddy Noviana; Hamizi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the problem of low yields third grade social studies students of SDN 005 Makmur. Causative factor of such students are passive students in learning activities, students do not develop material to a wider scope and students have not been able to associate the concepts that have been studied with everyday life. This research is an experimental research, the research was conducted 4 meetings and the control class 4 meetings experimental class, where before entering the first meeting of each class in different days, both classes are given about Pree test, and after the meeting to four each -masing classes are also given about the post-test. In this study, researchers applied the approach Contextual Teaching and Learning (CTL). Subjects were IIIa class, there are 26 students and class IIIb as many as 26 students. Implemented in the second semester of academic year 2014/2015 on 16 April to 15 May 2015. Data collection techniques include test results of study and documentation of learning activities. Having done the research and data analysis, that the results of the acquisition Pree disimpulkanlah test the experimental class with an average of 65.04 and the control class with an average of 59.57, the results of the test data processing Pree T test showed t ≤ t table or 0.135 ≤ 2.021, so Ho accepted and Ha rejected. In other words, the mean scores test Pree there are no significant differences in learning outcomes. While the results of the acquisition of post-test scores in the experimental class with an average of 75.65 and the control class with an average of 73.77 then the data processing post-test t test seen that t ≤ t table ≤ 2,021 or 0,066, so Ho accepted and Ha rejected. In other words, the mean score of post test results to learn there are no significant differences.Keywords : Approach Contextual Teaching and Learning (CTL), Influence learning outcomes of IPS studies